Mechanical behaviour of strain aged dual phase steels - Abdalla, A. J. [UNESP]; Hein, L. R O [UNESP]; Pereira, Marcelo dos Santos [UNESP]; Hashimoto, T. M. [UNESP] (My University, 1999)
Dual phase steels, characterised by good formability and excellent surface finish, are suitable for applications where processing involves cold deformation. In this context an investigation has been conducted into the cold deformation aging susceptibility of carbon steel API-5L-B and microalloyed steel API-5L-X52, both with dual phase microstructures. Changes in mechanical properties such as phase microhardness, ultimate tensile strength, and yield strength in both types of steel were observed at aging temperatures of 25, 80, and 150°C. This aging is associated with dislocation structures formed on ferrite grains in the vicinity of ferrite/martensite interfaces during intercritical treatments, which become preferential sites for solute atom diffusion. © 1999 IoM Communications Ltd.